Chinese-english translation strategies for metaphors based on domestication and foreignization - Tian, Dandan; Abdullah, Muhammad Alif Redzuan (2024)
As an essential rhetorical device in language expression, metaphor deeply reflects the cultural background and social cognition. Metaphor translation needs to convey the meaning of language as well as the cultural connotations behind the metaphor. This study found that when the metaphorical images contain the same symbolic meaning in Chinese and English cultures, applying foreignization to reproduce the original metaphorical images can maintain the uniqueness and writing style of the source text and avoid the loss of cultural connotations in the translation process. Instead, in the case of different metaphorical images, using domestication to replace or omit the original symbolic images in the target language can improve the readability and acceptance of the translation. However, no studies explore applying metaphor translation strategies based on comparing the similarities and differences of metaphors in different languages and cultures, causing subjectivity in selecting metaphor translation strategies. This study compares the symbolic meanings of metaphors in Chinese and English cultures and provides a reliable and objective basis for selecting domestication and foreignization for metaphor translation, which help to achieve more effective faithfulness and cultural transmission. This analysis provides practical references for translation strategies of metaphors and promotes the depth of cross-cultural communication